2001
DOI: 10.1111/j.1095-8649.2001.tb01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic introgression between wild and stocked brown trout in the Douro River basin, Spain

Abstract: The genetic diversity of Spanish brown trout is currently threatened by stocking with exogenous brown trout from Central and Northern Europe. In the Douro River basin 25% of the analysed populations in the present study showed introgression by genes of hatchery origin. The mean introgression estimated by the single locus approach (S |) varied from 0 to 22% among populations, with a mean value of 3%. The hatchery allele markers were absent in populations where stocking ceased in 1993. However, the introgression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Except for five comparisons involving Loobu samples, introgression estimate trueS^ (Taggart & Ferguson ; Almodovar et al . ) based on SNPs resulted in higher values compared to the alternative estimate I (Karlsson et al . ) based on admixture modelling and multilocus microsatellite genotype data.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Except for five comparisons involving Loobu samples, introgression estimate trueS^ (Taggart & Ferguson ; Almodovar et al . ) based on SNPs resulted in higher values compared to the alternative estimate I (Karlsson et al . ) based on admixture modelling and multilocus microsatellite genotype data.…”
Section: Discussionmentioning
confidence: 84%
“…Second, introgression was quantified from allele frequency shifts for each SNP marker based on the expression: trueS^ = ( p w ‐ p n ) × ( p h ‐ p n ) −1 , where p w , p h and p n are the allele frequencies of the wild population, the hatchery stock and the native population sample collected before large‐scale releases, respectively (Taggart & Ferguson ; Almodovar et al . ). To ensure that the locus‐specific and genomewide introgression estimates were as accurate as possible, for subsequent analysis, we used only a subset of SNPs (upper 30th percentile) that showed the highest genetic differentiation ( F ST ) between hatchery stock and the earliest wild samples.…”
Section: Methodsmentioning
confidence: 97%
“…Consequently, the knowledge of the habitat requirements of species is essential for assessing different impacts from human activities on fish communities. This is especially relevant in salmonid wild populations of south European countries which are currently threatened by habitat destruction, pollution, introduction of exotic especies, overfishing and introgression of foreign genes as a result of artificial stocking (Almodóvar and Nicola, 1998Almodóvar et al, 2001Almodóvar et al, , 2002Almodóvar et al, , 2006aElvira and Almodóvar, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…However, limitations in space and time associated with high effective costs have resulted many times in the low success rate of these activities. Furthermore, several studies have reported negative consequences of stocking such as the spread of parasites and diseases (MOFFIT et al, 1998), an increase of competitive interactions (NICKELSON et al, 1986;McMICHAEL and PEARSONS, 1997), and, more recently, genetic introgression (BLANCO et al, 1998;CAGIGAS et al, 1999;ALMODÓVAR et al, 2001). …”
Section: Introductionmentioning
confidence: 99%